The Theosophists and the International Organization of New Education (1911-1921) - Wagnon, Sylvain (2017)
The historic importance of Theosophy within the realm of education is due to their presence in their reflexions and educational endeavours are at the origins of that nebulous movement called the New Education (éducation nouvelle).  Their presence at the beginning of the organization of the New Education has been explored by several pioneering papers, but remains the blind spot in this area. In fact Theosophy’s influence has been felt but rarely analysed as the matrix of the nebulous international organization of new education.  If the Theosophists’ influence were to be recognised, we think that their role, their persistent work that brought on not only the rise of new education, more specifically, the constitution of the International League of New Education but was also the making of educators of Theosophy teachings such as Maria Montessori and Rudolf  Steiner who were not only the roots of the new education but also its main components.